Microwave-enhanced anodic stripping detection of lead in a river sediment sample. A mercury-free procedure employing a boron-doped diamond electrode - Tsai, Y; Coles, B; Holt, K; Foord, J; Marken, F; Compton, R (2001)
Microwave activation of electrochemical processes has recently been introduced as a novel technique for the enhancement and control of processes at the electrode-solution interface and is employed here to improve the analytical detection of Pb2+. Instead of the conventional mercury-based accumulation and stripping procedure, mercury-free boron-doped diamond electrodes are employed. The deposition and anodic stripping detection by square-wave voltammetry of Pb2+ in a 0.1 M HNO3 solution is shown to be strongly enhanced by microwave activation at boron-doped diamond electrode. The temperature at the electrode-solution interface is calibrated with reversible redox couple Fe3+/Fe2+ (4 mM Fe3+, 4 mM Fe2+) in 0.1 M HNO3 and a standard addition procedure is developed for the sensitive detection of Pb2+ concentrations from 1 μM to 5 μM. The limit of detection by square-wave voltammetry after 20 s deposition time was found to be 0.1 μM and 1.0 μM with microwave activation and without microwave activation, respectively. Then, the Pb content in a water sediment sample detected by anodic stripping voltammetry at boron-doped diamond electrodes is shown to be in good agreement with two other independent analytical procedures based on ICP mass spectroscopy and on sono-cathodic stripping voltammetry.